Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Let x be the age of John

Let 12 be the age of Edna

Edna's age is two times the age of John.

John's age is twice as the age of Edna.

Then, the age of John is the age of Edna divided by 2.

12 / 2 = x

6 = x

So therefore, John is 6 years old, twice as old as Edna.

Let 12 be the age of Edna

Edna's age is two times the age of John.

John's age is twice as the age of Edna.

Then, the age of John is the age of Edna divided by 2.

12 / 2 = x

6 = x

So therefore, John is 6 years old, twice as old as Edna.

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Let 'x' be John's age

let 'y' be Edna's age

----------

'john is twice as old as edna'

x = 2y ----equation 1

---------

'if edna is 12 years old'

y=12 -----equation 2

--------

substitute equation 2 to equation 1

x = 2y

x = 2(12)

x = 24

--------

therefore John is 24 years old

let 'y' be Edna's age

----------

'john is twice as old as edna'

x = 2y ----equation 1

---------

'if edna is 12 years old'

y=12 -----equation 2

--------

substitute equation 2 to equation 1

x = 2y

x = 2(12)

x = 24

--------

therefore John is 24 years old